Increased Level of c-kit in Semen of Infertile Patients with Varicocele - Jin, Guorong; Liu, Jianrong; Qin, Qin; Gao, Songdan; Zhang, Fang; Ma, Yuehong; Ding, Caiyun; Dong, Lina; Yin, Haizhen; Wang, Yimin (Urology Journal, 2017)
Purpose: Varicocele is the most common risk factor for male infertility, however, not all males with varicocele experience infertility. In fact, most patients with varicocele have normal spermatogenesis. The molecular mechanism of varicocele-associated infertility is yet to be completely understood. The aim of this study is to assess the association of a number of fertility regulatory factors on varicocele associated infertility and to throw light on the mechanism of varicocele-associated infertility. Materials and Methods: Semen from 30 infertile patients with varicocele and 30 fertile men with varicocele were collected. The concentrations of the following factors in seminal plasma were determined by ELISA: follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone (T), androgen binding protein (ABP), transferrin (Trf), inhibin B (INHB) and stem cell factor (SCF). The expression level of c-kit in seminal precipitate of patients with varicocele was detected by real-time PCR. Results: The concentrations of sexual hormones, FSH, LH and T, had no differences between infertile patients with varicocele and fertile men with varicocele (P > 0.05). Factors secreted by Sertoli cells, ABP, Trf, INHB and SCF, showed no significant differences between the two groups (P > 0.05). Interestingly, the expression of c-kit was significant higher in infertile patients with varicocele than that in fertile men with varicocele (P < 0.01). Conclusion: Neither the sexual hormones nor the Sertoli cells was responsible for the infertility induced by varicocele. The aberrant expression of c-kit in infertile patients with varicocele may provide new insight into the mechanism of varicocele-associated infertility.